Diversity of annelids in organic substrates in the deep Southwest Atlantic Ocean - Shimabukuro, Mauricio (2018)
This thesis aims to characterize the annelid diversity of whale bones implanted in the SW Atlantic at two different depths (1500 and 3300 m) and its relation with other whale falls and chemosynthetic environments. The first chapter presents a general introduction with a brief review on whale-fall composition and its importance to the deep-sea ecosystem. Chapter 1 also exhibits the distribution of annelid families showing that assemblages are probably under the control of oceanographic processes, such as water masses characteristics and direction of flow. The diversity of the most important whale fall specialist, Osedax, is explored in chapter 2. The distribution of Osedax species on the studied depths reinforces the importance of oceanographic processes for community structure. In this chapter we also compare Atlantic and Pacific populations of Osedax frankpressi. Interestingly, the family Capitellidae was the most abundant annelid in whale bones and, for this reason, the diversity of Capitella is evaluated in chapter 3, the only capitellid genus found in whale falls. The phylogenetic relationships of shallow-water and deep-sea Capitella are present in chapter 3, providing insights for the invasion and diversification of this genus in the deep-sea environment. In Chapter 4, the diversity and phylogeny of Sirsoe and Vrijenhoekia is investigated. The phylogenic analysis of both genera indicates the inclusion of Vrijenhoekia inside Sirsoe. Ten new Sirsoe species were found, some of them cryptic and some shared between Atlantic and Pacific whale falls. Only one new species was previously found in vents. Finally, chapter 5 highlights the contribution of this thesis to the knowledge of whale fall diversity, suggesting important issues for future studies.